Effect of Multiple Representations on Students’ Performance on Interpretations and Techniques of Representation in Calculus - Arefaine, Niguse; Michael, Kassa; Assefa, Shimelis (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2022)
This study investigated the effect of the multiple representations approaches on students’ representation interpretation in learning calculus. Pretest and posttest quasi-experimental design of non-equivalent groups was used. Three intact groups of size 53, 57, and 54 students from Jigjiga and Kebri-Dehar Universities in Ethiopia participated in this study. The groups included a GeoGebra-supported multiple representations approach (MRT) from Jigjiga University, a multiple representation approach (MR), and a conventional approach (CG), both from Kebri Dehar University. Representation interpretation problem pretest and posttest were administered compiled from pre and calculus contents, respectively. Students’ performance on representation interpretation problems was assessed using rubric scores, and their interpretation techniques were labeled as local versus global and syntactic versus semantic. Results revealed no statistically significant mean difference among the three groups on representation interpretation from the posttest that was determined by one-way ANOVA ((F(2.161) = 2.232, P = .111 , Partial eta = .03). More students in each group demonstrated local and semantic interpretation than global and syntactic interpretation. After the treatment, many students from each group shifted towards the local and semantic interpretation. It is recommended that the study need to replicate other calculus contents with different participants to generalize the results of the study.DOI: https://doi.org/10.22342/jpm.16.3.18291.351-372